Exploring Lincoln : great historians reappraise our greatest president - Williams, Frank J.; Symonds, Craig L.; Holzer, Harold (North's Civil War., 2015)
Despite the literally thousands of books that have been written about Abraham Lincoln, he continues to fascinate.